1993
DOI: 10.1093/clinids/17.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Association of Rhinovirus Infection with Poor Bacteriologic Outcome of Bacterial-Viral Otitis Media

Abstract: Viruses--both alone and in combination with bacteria--have been shown to be a cause of acute otitis media (AOM). Moreover, the presence of virus in middle ear fluid (MEF) interferes with the bacteriologic response to antibiotic treatment in AOM. We studied various factors related to the eradication of bacteria from the MEF of infants and children who had AOM associated with a combination of bacteria and viruses. Of 622 cases of AOM diagnosed and treated between 1985 and 1991, 71 were due to such a combination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 15 publications
2
23
1
Order By: Relevance
“…Notably, the presence of rhinovirus in middle ear fluid was associated with a significantly higher antibiotic failure rate (78%) than that associated with many other viruses, including respiratory syncytial virus (30%), enterovirus (17%), influenza virus (11%), and parainfluenza virus (10%). 36 Similar findings have been reported in other studies. 37,38 …”
Section: Acute Otitis Media and Rhinovirus Infectionsupporting
confidence: 88%
“…Notably, the presence of rhinovirus in middle ear fluid was associated with a significantly higher antibiotic failure rate (78%) than that associated with many other viruses, including respiratory syncytial virus (30%), enterovirus (17%), influenza virus (11%), and parainfluenza virus (10%). 36 Similar findings have been reported in other studies. 37,38 …”
Section: Acute Otitis Media and Rhinovirus Infectionsupporting
confidence: 88%
“…HRV has also been detected in the MEF; one recent study reported a high HRV detection rate in 58 % from children with a history of recurrent AOM [44]. HRV has also been associated with poor bacteriologic outcome for AOM treated with antibiotics, compared to other respiratory viruses [45]. …”
Section: Viral Upper Respiratory Tract Infectionmentioning
confidence: 99%
“…Human milk contains various factors with known antiviral or antibacterial activity in vitro [1,4]. Recently, respiratory syncytial virus (RSV) and, more particularly, rhinoviruses have been implicated in predisposing infants to and causing otitis media [5,6]. Rhinoviruses also cause middle ear problems in adults [7].…”
Section: Introductionmentioning
confidence: 99%